SPECTRA – a Maple library for solving linear matrix inequalities in exact arithmetic. (2nd January 2019) - Henrion, Didier; Naldi, Simone; Safey El Din, Mohab
Abstract : This document describes our freely distributed Maple libraryspectra, for Semidefinite Programming solved Exactly with Computational Tools of Real Algebra. It solves linear matrix inequalities with symbolic computation in exact arithmetic and it is targeted to small-size, possibly degenerate problems for which symbolic infeasibility or feasibility certificates are required.